The effects of trust on parasocial interaction of Malaysian facebook (FB) travel community - Abdul Latif, Samshul Amry; Abdul Aziz, Nadiatul Husna (IGI Global, 2021)
This chapter investigates the effects of trust dimension (competence, benevolence, and honesty) on parasocial interaction (PSI) of a Malaysian travel community through the usage of social media platforms. This study utilized a non-probability purposive sampling approach targeting Malaysians who use FB to interact and share their travel activities using self-administered online survey approach. Based on 142 respondents, the data were analyzed using multiple regression. The findings suggest that all three dimensions under trust are significant in predicting PSI among Malaysian FB travel community. The limitation of the study is that the majority of the samples were females and limited to only one FB community group.